Peculiar enhancement in the neutral K and Na layers observed during atypical E-region event in the South American magnetic anomaly (SAMA) region - Andrioli, Vania F.; Xu, Jiyao; Batista, Paulo P.; Resende, Laysa C. A.; Da Silva, Ligia A.; Pimenta, Alexandre A.; Martins, Maria P. P.; Santos, Angela M.; Moro, Juliano; Vieira, Luis; Chen, Sony S.; Yang, Guotao; et al. (Frontiers in Astronomy and Space Sciences, 2024)
The sudden enhancement in the mesospheric neutral metal layers (Ns) has been studied in different latitudes for decades. Specifically, at 23°S, Sodium Ns layers have been analyzed since their first observation at the end of the seventies. Several studies have reported Sodium Ns during events of energetic particle precipitation (EPP) and the formation of auroral-type sporadic E (Esa) layers at high-latitude stations. The Esa layers are also observed in the Brazilian low-latitude sector during the EPP events due to the South American Magnetic Anomaly (SAMA). However, despite extensive studies on the SAMA region, no reports exist about the co-occurrence of the Ns layer and the Esa layer. Therefore, in the present work, for the first time, we observed on 26 April 2023 a peculiar Ns layer event synchronously occurring with the development of the Esa layer in the SAMA region.